Solid electrolytic capacitor
By controlling the pH value of the dissolution solution of the sealing material to be above 6.0 and below 8.1, neutralizing the acid component in the solid electrolytic capacitor, the problems of cathode corrosion and electrostatic capacity reduction in high temperature and high humidity environment are solved, and stable electrostatic capacity is achieved.
Patent Information
- Application Number
- CN202380065174.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-13
- Filing Date
- 2023-09-12
- Publication Date
- 2025-04-18
AI Technical Summary
When solid electrolytic capacitors are used in high temperature and high humidity environments, the freeness of the acid component leads to corrosion of the cathode part, reducing conductivity and reducing electrostatic capacity.
By immersing the sealing material in water or methanol aqueous solution with a pH of 7.0, the pH value of the water or methanol aqueous solution after being heated to be controlled to be 6.0 or above and 8.1 or below to neutralize the acid component and inhibit corrosion of the cathode part.
When voltage is applied in high temperature and high humidity environments, the electrostatic capacity is difficult to reduce, ensuring the stable performance of the solid electrolytic capacitor.
Smart Images

Figure CN119856241A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a solid electrolytic capacitor including a capacitor element. Background Art
[0002] Patent document 1 proposes "a method for manufacturing a capacitor, which has the following steps: a step of supplying an anode having a dielectric thereon; a step of supplying a first layer of a conductive polymer to the dielectric to form a capacitor precursor; a step of supplying other layers of one or more conductive polymers from a dispersion on the first layer; and a step of treating the capacitor precursor at a temperature of 50°C to 200°C and a relative humidity of 25 to 100%".
[0003] Patent Document 2 describes that aluminum hydroxide, magnesium hydroxide, zinc borate, and the like can be used as inorganic fillers having a flame retardant effect in epoxy resin molding materials for electronic component sealing.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application No. 2016-522573
[0007] Patent Document 2: Japanese Patent Application Laid-Open No. 10-259292 Summary of the invention
[0008] Problem that the invention aims to solve
[0009] Solid electrolytic capacitors that can be used in harsh high-temperature and high-humidity environments are being sought. However, the solid electrolyte of solid electrolytic capacitors contains acid components. When a voltage is applied to the solid electrolytic capacitor under high temperature and high humidity, the acid components are liberated and sometimes corrode the cathode. As a result, the conductivity of the cathode is reduced and the electrostatic capacitance is reduced.
[0010] Solutions for solving problems
[0011] One aspect of the present disclosure relates to a solid electrolytic capacitor, comprising: a capacitor element, comprising an anode portion and a cathode portion; an anode lead frame, connected to the anode portion; a cathode lead frame, connected to the cathode portion; and an insulating sealing material, covering the capacitor element and partially covering the anode lead frame and the cathode lead frame, respectively, wherein the capacitor element comprises a solid electrolyte, 5 g of the sealing material is immersed in 50 cc (50 mL) of water or methanol aqueous solution with a pH value of 7.0 in a pressure-resistant container, and the pH value of the water or methanol aqueous solution after heating at 121° C. for 24 hours is greater than 6.0 and less than 8.1.
[0012] Another aspect of the present disclosure relates to a solid electrolytic capacitor, comprising: a capacitor element, comprising an anode portion and a cathode portion; an anode lead frame, connected to the anode portion; a cathode lead frame, connected to the cathode portion; and an insulating sealing material, covering the capacitor element and partially covering the anode lead frame and the cathode lead frame, respectively, wherein the capacitor element comprises a solid electrolyte, and the sealing material is immersed in water or a methanol aqueous solution having a pH value of 7.0 in a pressure-resistant container and heated until the pH value of the water or the methanol aqueous solution after saturation of the eluted components from the sealing material exceeds 7.
[0013] Effects of the Invention
[0014] According to the present disclosure, it is possible to provide a solid electrolytic capacitor whose electrostatic capacitance is unlikely to decrease even when a voltage is applied in a high-temperature and high-humidity environment.
[0015] While the novel features of the present invention are described in the appended claims, the present invention will be better understood from the following detailed description both as to structure and content and in conjunction with other objects and features of the present invention and with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a cross-sectional view schematically showing an example of a capacitor element of an electrolytic capacitor according to an embodiment of the present disclosure.
[0017] Figure 2 It is a cross-sectional view schematically showing an electrolytic capacitor according to one embodiment of the present disclosure. DETAILED DESCRIPTION
[0018] Below, examples are given to illustrate the implementation of the solid electrolytic capacitor involved in the present disclosure, but the present disclosure is not limited to the examples described below. In the following description, specific numerical values and materials are sometimes given as examples, but other numerical values and materials may also be used as long as the effects of the present disclosure can be obtained. In this specification, the description of "numerical value A to numerical value B" includes numerical value A and numerical value B, and can be read as "above numerical value A and below numerical value B". In the following description, when the lower limit and upper limit of numerical values related to specific physical properties, conditions, etc. are given as examples, as long as the lower limit is not above the upper limit, any of the exemplified lower limits can be arbitrarily combined with any of the exemplified upper limits. When multiple materials are given as examples, one can be selected and used alone, or two or more can be used in combination.
[0019] In addition, the present disclosure includes a combination of the contents of two or more claims arbitrarily selected from the plurality of claims recorded in the appended claims. In other words, the contents of two or more claims arbitrarily selected from the plurality of claims recorded in the appended claims may be combined as long as no technical contradiction occurs.
[0020] "Solid electrolytic capacitor" can be read as "electrolytic capacitor" and "capacitor" can be read as "capacitor".
[0021] The solid electrolytic capacitor disclosed herein comprises a capacitor element, which comprises an anode portion and a cathode portion. The solid electrolytic capacitor may have only one capacitor element, or may have a plurality of stacked capacitor elements. The capacitor element may be formed of a foil of a valve metal, or may be formed of a sintered body of a valve metal powder. The capacitor element comprises a solid electrolyte. The solid electrolyte comprises, for example, a conductive polymer, and the conductive polymer comprises a dopant.
[0022] The anode portion is electrically connected to an anode lead frame. The cathode portion is electrically connected to a cathode lead frame. Other conductive components may be interposed between the anode lead frame and the anode portion. For example, when the anode portion includes a sintered body, a rod-shaped wire is embedded in the sintered body, and a portion of the wire stands upright from the sintered body. In this case, the anode lead frame is connected to the upright portion of the wire. The lead frame may be composed of, for example, a bent metal flat plate or metal sheet.
[0023] The solid electrolytic capacitor includes an insulating sealing material covering the capacitor element and partially covering the anode lead frame and the cathode lead frame. The portions of the anode lead frame and the cathode lead frame not covered by the sealing material function as the anode external terminal and the cathode external terminal.
[0024] The sealing material is not particularly limited, but is generally a cured product of a thermosetting resin composition. Hereinafter, regardless of whether it is cured, the thermosetting resin composition is sometimes collectively referred to as a sealing material. The resin composition, for example, includes a main resin, a curing agent that reacts with the main resin, and a filler, and may include various additives. As additives, curing accelerators, ion traps, coupling agents, pigments, carbon black, etc. may be listed, but are not limited to these.
[0025] The cured product (sealing material) of a thermosetting resin composition is usually acidic, and its pH value is at least less than 6, and is mostly around 4. Assuming that the sealing material is immersed in water or methanol aqueous solution with a pH value of 7.0 in a pressure-resistant container, and the pH value of the water or methanol aqueous solution is heated to a basic value exceeding 8.1 after saturation of the eluted components from the sealing material, the physical properties of the sealing material will be impaired. Such a sealing material with a strong alkalinity is easy to gel in an uncured state, and on the other hand, the curing reaction cannot be fully carried out even if heated for a long time. For example, in the case where 5g of sealing material is immersed in 50cc of water or methanol aqueous solution with a pH value of 7.0 in a pressure-resistant container, if it is heated at 121°C for 24 hours in the pressure-resistant container, the water or methanol aqueous solution can be saturated with the eluted components from the sealing material.
[0026] On the other hand, the pH of the solidified material can be raised to near neutrality. The sealing material used in the solid electrolytic capacitor of the present disclosure is immersed in water or methanol aqueous solution in a pressure-resistant container, and heated until the pH value of the water after saturation of the dissolved components from the sealing material (hereinafter also referred to as "eluate pH value") is controlled to be above 6.0 and below 8.1 (i.e., neutral or near neutral).
[0027] By controlling the pH value of the dissolving solution to be above 6.0 and below 8.1, even when the acid component (such as a dopant) in the solid electrolyte is free, the acid component will be neutralized, and the reduction in conductivity and the reduction in electrostatic capacity caused by the corrosion of the cathode portion can be suppressed. The pH value of the dissolving solution is preferably above 6.5 and may also exceed 7. For example, the pH value of the dissolving solution may be a weak alkaline of above 7.1. In this case, since the acid component is rapidly neutralized, the corrosion of the cathode portion is significantly suppressed.
[0028] The method for controlling the pH value of the eluate to be greater than 6.0 and less than 8.1 is not particularly limited. For example, a filler that is alkaline in water may be used. Examples of such fillers include inorganic powders such as metal hydroxides.
[0029] As the metal hydroxide, for example, at least one of magnesium hydroxide and aluminum hydroxide is preferably used. They are cheap and will not make the pH value of the dissolution solution too alkaline, and it is easy to control the pH value of the dissolution solution to be above 6.0 and below 8.1, or above 6.5 and below 8.1, or above 7.1 and below 8.0. It can be considered that when the acid component in the solid electrolyte is free, the metal hydroxide generates hydroxide ions to capture the acid component.
[0030] The sealing material preferably contains inorganic powders other than metal hydroxides as fillers. When the fillers are mostly metal hydroxides, the alkalinity of the sealing material is sometimes too high. On the other hand, when a metal hydroxide and an inorganic powder other than metal hydroxide are used in combination as fillers, it is easy to control the pH value of the sealing material to the weak alkalinity as described above.
[0031] As inorganic powders other than metal hydroxides, for example, metal oxides can be used. As the metal oxide, it is preferred to use at least one selected from the group consisting of aluminum oxide, magnesium oxide, silicon oxide, titanium oxide, and zirconium oxide. Among them, silicon oxide (silicon dioxide) is preferred, and spherical fused silica is particularly preferred.
[0032] From the perspective of easily controlling the pH value of the dissolution solution of the sealing material, the content of the inorganic powder other than the metal hydroxide contained in the sealing material is preferably greater than the content of the metal hydroxide. For example, it is preferred that more than 50% by mass of the filler is the inorganic powder other than the metal hydroxide. More than 90% by mass of the inorganic powder other than the metal hydroxide can be a metal oxide. In addition, it is preferred that more than 5% by mass and less than 30% by mass of the filler is the metal hydroxide.
[0033] From the perspective of improving strength, the content of the filler in the sealing material is, for example, 70% by mass or more, 75% by mass or more, or 80% by mass or more. When the viscosity of the sealing material before curing is taken into account, the content of the filler in the sealing material can be, for example, 90% by mass or less.
[0034] As another method for controlling the pH value of the sealing material dissolution solution to be greater than 6.0 and less than 8.1, for example, an ion capture agent that is alkaline in water may be used. For example, by using an ion capture agent that is alkaline in water in an amount greater than the general usage, the pH value of the sealing material dissolution solution may be controlled to be greater than 6.0 and less than 8.1. In addition, the alkaline ion capture agent may be used alone, or a metal hydroxide and such an ion capture agent may be used in combination.
[0035] The sealing material or thermosetting resin composition can be formed into a predetermined shape and cured using molding techniques such as injection molding, insert molding, compression molding, etc. For example, the sealing material or thermosetting resin composition is filled into a predetermined mold and heated so that it covers the outer surface of the capacitor element and a portion of each lead frame.
[0036] As the main resin, for example, epoxy resin, phenolic resin, urea resin, polyimide resin, polyamide-imide resin, polyurethane resin, diallyl phthalate resin, unsaturated polyester resin, etc. can be listed. The main resin can be used alone or in combination. Among them, epoxy resin is preferred.
[0037] The epoxy resin is not particularly limited, and biphenyl epoxy resin, bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol AD epoxy resin, naphthalene epoxy resin, glycidylamine epoxy resin, novolac epoxy resin, alicyclic epoxy resin, dicyclopentadiene epoxy resin, polyether epoxy resin, silicone-modified epoxy resin, etc. can be used. These can be used alone or in combination of two or more.
[0038] The curing agent is not particularly limited, but preferably used are phenol resins, acid anhydrides, aliphatic or aromatic amines, imidazole, imidazole derivatives, and the like.
[0039] Examples of the curing accelerator include dicyandiamide and the like.
[0040] It should be noted that the pH value of the sealing material can be measured by the following method.
[0041] First, separate only the sealing material (solidified material) from the solid electrolytic capacitor. Immerse the sealing material in an appropriate amount of water (preferably ion exchange water or pure water) with a pH value of 7.0 and place it in a pressure-resistant container. Secondly, heat until the dissolved components from the sealing material are saturated. For example, in a pressure-resistant container, immerse the sealing material in water and fully heat it under the conditions described below. Then, use a commercially available pH tester to measure the pH of the water in the pressure-resistant container (i.e., the pH value of the dissolution solution). When the pH value exceeds 7.0, it can be said that the sealing material itself is alkaline.
[0042] The water contained in the pressure-resistant container may contain methanol to promote the dissolution of the components in the sealing material. That is, the pH value of the dissolution liquid may be the pH value of the methanol aqueous solution. The methanol concentration is not particularly limited, and for example, an aqueous solution containing methanol at a content of 5 to 10% by mass (preferably 8% by mass) may be used. The methanol in such a methanol aqueous solution does not affect the pH of the water. If the pH value of the water constituting the methanol aqueous solution is 7.0, the pH value of the methanol aqueous solution is also 7.0.
[0043] In order to saturate the eluted components from the sealing material with respect to the water or methanol aqueous solution in the pressure container, for example, 5 g of the sealing material is weighed, placed in a pressure container together with 50 cc of water or methanol aqueous solution with a pH value of 7.0, and heated at 121°C for 24 hours. Then, the pH of the water or methanol aqueous solution in the pressure container is measured using a commercially available pH tester. If the resulting pH value is greater than 6.0 and less than 8.1, it can be said that the sealing material is neutral or near neutral. In addition, when the resulting pH value exceeds 7.0, it can be said that the sealing material changes from neutral to weakly alkaline.
[0044] In the past, the capacity change rate under high temperature and high humidity environment was measured under 85℃ / 85% relative humidity. When voltage is continuously applied to a solid electrolytic capacitor under 85℃ / 85% relative humidity environment, for example, if it is continuously applied for 132 hours, the electrostatic capacitance will not change significantly even if the pH value of the sealing material dissolution solution is less than 6.0 acidic.
[0045] However, in recent years, experiments have been conducted to use solid electrolytic capacitors in more severe high-temperature and high-humidity environments. For example, a test was conducted in which a voltage was continuously applied to a solid electrolytic capacitor at a high temperature of 110°C and a relative humidity of 85%. In this case, the electrostatic capacitance of the solid electrolytic capacitor changes greatly depending on the pH value of the elution solution of the sealing material.
[0046] When the pH value of the sealing material's dissolving solution is less than 6, the electrostatic capacitance decreases significantly when a voltage is applied to the solid electrolytic capacitor for 132 hours at 110°C / 85% relative humidity. On the other hand, when the pH value of the sealing material's dissolving solution is 6.0 or more, the electrostatic capacitance decreases slightly when a voltage is applied to the solid electrolytic capacitor for 132 hours at 110°C / 85% relative humidity, and the difference is significant.
[0047] It should be noted that the reduction in electrostatic capacitance when a voltage is applied to a solid electrolytic capacitor having a pH value of less than 6.0 of the dissolution of the sealing material for 132 hours under an environment of 110°C / relative humidity 85% is the same as the reduction in electrostatic capacitance when a voltage is applied to the same solid electrolytic capacitor for 1000 hours under an environment of 85°C / relative humidity 85%.
[0048] As described above, the reduction of electrostatic capacitance under high temperature and high humidity environment is a new problem that has emerged in the process of developing solid electrolytic capacitors that are required to be used under more severe conditions than before. On the other hand, by making the pH value of the dissolution solution of the sealing material 6.0 or more, further 6.5 or more, and further more than 7.0 weakly alkaline, it is possible to obtain a solid electrolytic capacitor that can fully withstand use under severe conditions.
[0049] 《Electrolytic Capacitors》
[0050] Hereinafter, an example of a solid electrolytic capacitor and a method for manufacturing the same according to the present disclosure will be described with reference to the drawings as appropriate. However, the present disclosure is not limited thereto. Figure 1 This is a cross-sectional view schematically showing an example of a capacitor element of a solid electrolytic capacitor according to the present disclosure. Figure 2 It is a schematic cross-sectional view of an example of the solid electrolytic capacitor involved in the present disclosure.
[0051] The solid electrolytic capacitor 20 includes a capacitor element 10 having an anode portion 6 and a cathode portion 7, an outer casing (sealing material) 11 sealing the capacitor element 10, an anode lead frame 13 electrically connected to the anode portion 6 and partially exposed from the outer casing 11, and a cathode lead frame 14 electrically connected to the cathode portion 7 and partially exposed from the outer casing 11. The anode portion 6 includes an anode body 1 and an anode wire 2. A dielectric layer 3 is formed on the surface of the anode body. The cathode portion 7 includes a solid electrolyte layer 4 covering at least a portion of the dielectric layer 3 and a cathode layer 5 covering at least a portion of the surface of the solid electrolyte layer 4.
[0052] <Capacitor Components>
[0053] Hereinafter, capacitor element 10 will be described in detail by taking the case where a solid electrolyte layer is provided as an electrolyte as an example.
[0054] The anode portion 6 includes an anode body 1 and an anode wire 2 extending from one surface of the anode body 1 and electrically connected to an anode lead frame 13 .
[0055] The anode body 1 is, for example, a porous sintered body of a rectangular parallelepiped obtained by sintering metal particles. As the metal particles, particles of valve metals such as titanium (Ti), tantalum (Ta), and niobium (Nb) can be used. One or more metal particles are used in the anode body 1. The metal particles can be an alloy containing two or more metals. For example, an alloy containing a valve metal and silicon, vanadium, boron, etc. can be used. In addition, a compound containing a valve metal and a typical element such as nitrogen can also be used. The alloy of the valve metal contains the valve metal as a main component, for example, contains more than 50 atomic % of the valve metal.
[0056] The anode wire 2 is made of a conductive material. The material of the anode wire 2 is not particularly limited, and for example, in addition to the above-mentioned valve-acting metals, copper, aluminum, aluminum alloys, etc. can also be listed. The materials constituting the anode body 1 and the anode wire 2 can be of the same type or different types. The anode wire 2 has a first portion 2a buried in the interior of the anode body 1 from one side of the anode body 1 and a second portion 2b extending from the above-mentioned side of the anode body 1. The cross-sectional shape of the anode wire 2 is not particularly limited, and a circular shape, a track shape (a shape consisting of parallel straight lines and two curved lines connecting the ends of these straight lines), an ellipse, a rectangle, a polygon, etc. can be listed.
[0057] The anode part 6 is produced, for example, by pressing and molding the first part 2a into a rectangular parallelepiped shape and sintering the first part 2a while burying the first part 2a in a powder of particles of the first metal. As a result, the second part 2b of the anode lead 2 is led out from one side of the anode body 1 in an upright manner. The second part 2b is joined to the anode lead terminal 13 by welding or the like, and the anode lead 2 is electrically connected to the anode lead terminal 13. The welding method is not particularly limited, and examples thereof include resistance welding, laser welding, and the like.
[0058] A dielectric layer 3 is formed on the surface of the anode body 1. The dielectric layer 3 is composed of, for example, a metal oxide. As a method for forming a layer composed of a metal oxide on the surface of the anode body 1, for example, a method of immersing the anode body 1 in a chemical conversion solution to anodize the surface of the anode body 1, and a method of heating the anode body 1 in an atmosphere containing oxygen can be cited. The dielectric layer 3 is not limited to the above-mentioned layer composed of a metal oxide, and any dielectric layer 3 may be used as long as it has insulating properties.
[0059] Anode body 1 is not limited to a porous sintered body, and may be, for example, a metal foil of a valve-acting metal such as aluminum foil.
[0060] (Cathode)
[0061] The cathode portion 7 includes a solid electrolyte layer 4 and a cathode layer 5 covering the solid electrolyte layer 4. The solid electrolyte layer 4 is formed so as to cover at least a portion of the dielectric layer 3.
[0062] In the solid electrolyte layer 4, for example, a manganese compound or a conductive polymer is used. As the conductive polymer, polypyrrole, polythiophene, polyfuran, polyaniline, polyacetylene, etc. can be listed. They can be used alone or in combination. In addition, the conductive polymer can also be a copolymer of two or more monomers. From the perspective of excellent conductivity, it can be polythiophene, polyaniline, or polypyrrole. In particular, from the perspective of excellent water repellency, it can be polypyrrole.
[0063] The solid electrolyte layer 4 containing a conductive polymer can be composed of two or more solid electrolyte layers. For example, the solid electrolyte layer 4 includes a first conductive polymer layer covering the dielectric layer 3 and a second conductive polymer layer covering the first conductive polymer layer. In the case where the solid electrolyte layer 4 is composed of two or more layers, the composition, formation method (polymerization method), etc. of the conductive polymer used in each layer may be different. For example, the first conductive polymer layer can be formed by polymerizing the raw material monomer on the dielectric layer 3. Alternatively, the second conductive polymer layer can be formed by applying a liquid containing the above-mentioned conductive polymer on the dielectric layer 3.
[0064] It should be noted that, in this specification, polypyrrole, polythiophene, polyfuran, polyaniline, etc. refer to polymers with polypyrrole, polythiophene, polyfuran, polyaniline, etc. as basic skeletons, respectively. Therefore, polypyrrole, polythiophene, polyfuran, polyaniline, etc. may include their respective derivatives. For example, polythiophene includes poly(3,4-ethylenedioxythiophene) and the like.
[0065] In order to improve the conductivity of the conductive polymer, various dopants may be added to the polymer solution, conductive polymer solution or dispersion for forming the conductive polymer. The dopant is not particularly limited, and examples thereof include naphthalenesulfonic acid, p-toluenesulfonic acid, polystyrenesulfonic acid and the like.
[0066] When the conductive polymer is dispersed in the dispersion medium in the form of particles, the average particle size D50 of the particles is, for example, 0.01 μm to 0.5 μm. When the average particle size D50 of the particles is within this range, the particles can easily penetrate into the inside of the anode body 1 .
[0067] Although in Figure 1 and Figure 2 Although not shown in the figure, since the anode body 1 is porous, the dielectric layer 3 is formed in a manner that covers the inner wall of the pores of the porous anode body 1, and the solid electrolyte layer 4 is formed in a manner that blocks the pores of the anode body 1 and penetrates deep into the interior of the porous anode body 1 (for example, until the area near the anode wire 2).
[0068] The cathode layer 5, for example, includes a carbon layer 5a formed in a manner covering the solid electrolyte layer 4 and a metal paste layer 5b formed on the surface of the carbon layer 5a. The carbon layer 5a includes a conductive carbon material such as graphite and a resin. The metal paste layer 5b includes, for example, metal particles (for example, silver) and a resin. It should be noted that the structure of the cathode layer 5 is not limited to this structure. The structure of the cathode layer 5 can be any structure as long as it has a current collection function.
[0069] <Anode lead frame>
[0070] The anode lead frame 13 is electrically connected to the anode body 1 via the second portion 2b of the anode wire 2. The material of the anode lead frame 13 is electrochemically and chemically stable, and is not particularly limited as long as it has conductivity. The anode lead frame 13 can be, for example, a metal such as copper, or a non-metal. If its shape is a flat plate, there is no particular limitation. From the perspective of low height, the thickness of the anode lead frame 13 (the distance between the main surfaces of the anode lead frame 13) can be greater than 25 μm and less than 200 μm, or can be greater than 25 μm and less than 100 μm.
[0071] One end of the anode lead frame 13 may be bonded to the anode wire 2 by a conductive adhesive material or solder, or may be bonded to the anode wire 2 by resistance welding or laser welding. The other end of the anode lead frame 13 is led out of the outer casing 11 and exposed from the outer casing 11. The conductive adhesive material is, for example, a mixture of a thermosetting resin and carbon particles or metal particles.
[0072] <Cathode lead frame>
[0073] Cathode lead frame 14 is electrically connected to cathode portion 7 at bonding portion 14a. Bonding portion 14a is a portion of cathode lead frame 14 that overlaps cathode layer 5 when cathode layer 5 and cathode lead frame 14 bonded thereto are viewed from the normal direction of cathode layer 5.
[0074] The cathode lead frame 14 is bonded to the cathode layer 5 via, for example, a conductive adhesive 8. One end of the cathode lead frame 14 constitutes, for example, a part of the bonding portion 14a, and is disposed inside the outer casing 11. The other end of the cathode lead frame 14 is led out to the outside. Therefore, a part of the cathode lead frame 14 including the other end is exposed from the outer casing 11.
[0075] The material of the cathode lead frame 14 is not particularly limited as long as it is electrochemically and chemically stable and has conductivity. The cathode lead frame 14 can be, for example, a metal such as copper, or a non-metal. Its shape is also not particularly limited, for example, it can be a long strip and flat plate. From the perspective of low height, the thickness of the cathode lead frame 14 can be greater than 25 μm and less than 200 μm, or can be greater than 25 μm and less than 100 μm.
[0076] <Exterior body>
[0077] The outer casing 11 is made of the above-mentioned sealing material and is provided to electrically insulate the anode lead frame 13 from the cathode lead frame 14 .
[0078] 《Method for manufacturing electrolytic capacitor》
[0079] Hereinafter, an example of a method for manufacturing a solid electrolytic capacitor according to the present disclosure will be described.
[0080] (1) Preparation process of capacitor elements
[0081] First, prepare a capacitor element. The process of preparing the capacitor element includes, for example, the following processes: a process of preparing an anode body; a process of covering at least a portion of the anode body with a dielectric layer; a process of covering at least a portion of the dielectric layer with a solid electrolyte layer; and a process of covering at least a portion of the solid electrolyte layer with a carbon layer. The process of preparing the capacitor element may also include a process of covering at least a portion of the carbon layer with a conductive resin layer (conductive paste layer).
[0082] (1a) Anode body preparation process
[0083] As the anode body 1, a porous sintered body can be used. Valve metal particles and anode wire 2 are placed in a mold in a manner such that the first part 2a is embedded in the valve metal particles, and sintered after pressure molding, thereby obtaining an anode part 6 of the anode body 1 containing a porous body as a valve metal. The first part 2a of the anode wire is embedded in the porous sintered body from one side. The pressure during pressure molding is not particularly limited. Sintering is preferably carried out under reduced pressure. A binder such as polyacrylic carbonate can be mixed with the valve metal particles as needed.
[0084] The valve-acting metal particles are usually pressure-molded and sintered using a mold having a rectangular inner space. In this case, the anode body 1 after sintering is also in the shape of a rectangular parallelepiped and has a plurality of main surfaces.
[0085] (1b) Dielectric layer formation step
[0086] Next, the anode body 1 is subjected to a chemical conversion treatment, and at least a portion of the anode body 1 is covered with a dielectric layer 3. Specifically, the anode body 1 is immersed in a chemical conversion tank filled with an electrolytic aqueous solution (e.g., a phosphoric acid aqueous solution), and the second portion 2b of the anode lead 2 is connected to the anode body of the chemical conversion tank, and anodization is performed, thereby forming a dielectric layer 3 composed of an oxide film of a valve-acting metal on the surface of the porous portion. The electrolytic aqueous solution is not limited to a phosphoric acid aqueous solution, and nitric acid, acetic acid, sulfuric acid, etc. can be used.
[0087] (1c) Solid Electrolyte Layer Formation Step
[0088] Next, at least a portion of dielectric layer 3 is covered with solid electrolyte layer 4. Thus, capacitor element 10 including anode body 1, dielectric layer 3 and solid electrolyte layer 4 is obtained. Solid electrolyte layer 4 including a plurality of conductive polymer layers may be formed.
[0089] As an example of forming a solid electrolyte layer 4 comprising multiple conductive polymer layers, the process for forming the solid electrolyte layer may also include the following steps: step (i), impregnating the anode body with a first solution comprising a first monomer which is a raw material of the first conductive polymer, polymerizing the first monomer on the surface of the dielectric layer, and forming a first conductive polymer layer covering the dielectric layer; and step (ii), impregnating the anode body with a solution or dispersion comprising a second conductive polymer, and forming a second conductive polymer layer covering the first conductive polymer layer.
[0090] In step (i), the first conductive polymer layer is formed on the anode body 1 formed with the dielectric layer 3 by impregnating the monomer or oligomer and polymerizing the monomer or oligomer by chemical polymerization or electrolytic polymerization. The first conductive polymer may also contain a dopant. The conductive polymer and the dopant may be selected from the conductive polymers and dopants exemplified for the solid electrolyte layer 4, respectively.
[0091] In the step (i) of forming the first conductive polymer layer, the raw material monomers of the first conductive polymer are oxidatively polymerized on the dielectric layer 3 (so-called "in-situ polymerization") to form the first conductive polymer layer on the dielectric layer 3. Therefore, fine irregularities due to uneven polymerization reaction or uneven layer growth may occur on the surface of the first conductive polymer layer.
[0092] In step (ii), the anode body is impregnated with a solution or dispersion containing a second conductive polymer, and the surface of the first conductive polymer layer is covered with the second conductive polymer layer. The second conductive polymer layer is formed in a manner that enters the concave portion of the surface of the first conductive polymer layer, and the adhesion between the first conductive polymer layer and the second conductive polymer layer is improved.
[0093] Prior to step (ii), the anode body on which the first conductive polymer layer is formed may be cleaned to remove unnecessary components such as unreacted monomers, dopants, and oxidants contained in the first conductive polymer layer.
[0094] After step (ii), the anode body may be impregnated with a solution or dispersion containing the third conductive polymer to form a third conductive polymer layer covering the second conductive polymer layer.
[0095] The second conductive polymer may also contain a dopant. As the conductive polymer and the dopant, they may be selected from the conductive polymers and dopants exemplified for the solid electrolyte layer 4, respectively. As the binder, a known binder may be used. The dispersion may contain a known additive used when forming the solid electrolyte layer.
[0096] After the conductive polymer layer is formed, a step of impregnating the solid electrolyte layer 4 with a salt compound is performed. When the salt compound is an ionic liquid, the salt compound can be impregnated by immersing the anode body 1 formed with the conductive polymer layer in the ionic liquid of the salt compound. Alternatively, the anode body 1 formed with the conductive polymer layer can be immersed in a liquid mixed with an ionic liquid and other solvents. The salt compound can be impregnated into the solid electrolyte layer under a reduced pressure atmosphere.
[0097] (1d) Cathode Layer Formation Step
[0098] Next, a carbon paste and a metal paste are sequentially applied on the surface of the solid electrolyte layer 4 to form a cathode layer 5 composed of a carbon layer 5a and a conductive resin layer (metal paste layer) 5b. The structure of the cathode layer 5 is not limited thereto, and any structure may be used as long as it has a current collecting function.
[0099] (2) Electrical connection process between capacitor element and lead frame
[0100] Next, the anode lead frame 13 and the cathode lead frame 14 are prepared. The second portion 2b of the anode wire 2 standing upright from the anode body 1 is joined to the anode lead frame 13 by laser welding, resistance welding, etc. In addition, after the conductive adhesive material 8 is applied to the cathode layer 5, the cathode lead frame 14 is joined to the cathode portion 7 via the conductive adhesive material 8.
[0101] Next, the capacitor element 10 and the sealing material (uncured thermosetting resin composition) forming the outer body 11 with a pH value of the dissolution solution of 6.0 or more and 8.1 or less are placed in a mold, and the capacitor element 10 is sealed by transfer molding, compression molding, etc. At this time, a portion of the anode lead frame 13 and the cathode lead frame 14 are exposed from the mold. The molding conditions are not particularly limited, as long as the time and temperature conditions are appropriately set in consideration of the curing temperature of the sealing material used.
[0102] Finally, the exposed portions of anode lead frame 13 and cathode lead frame 14 are bent along outer casing 11 to form bent portions. Thus, a portion of anode lead frame 13 and cathode lead frame 14 is disposed on the mounting surface of outer casing 11. Electrolytic capacitor 20 is manufactured by the above method.
[0103] [Example]
[0104] Hereinafter, embodiments of the technical solutions according to the present disclosure will be described in detail based on examples and comparative examples, but the present invention is not limited to the following examples.
[0105] 《Examples 1 to 7》
[0106] A solid electrolytic capacitor was manufactured according to the following procedure.
[0107] (Formation of Anode Body)
[0108] Tantalum metal particles are used as valve metal. The tantalum metal particles are molded into a rectangular parallelepiped in such a way that one end of an anode wire composed of tantalum metal is buried in the tantalum metal particles, and the molded body is sintered in a vacuum. Thus, an anode body composed of a porous sintered body of tantalum and an anode portion of the anode wire having one end buried in the anode body and the other end standing upright from one side of the anode body are obtained.
[0109] Next, the anode body and a portion of the anode lead extending from the anode body are immersed in a chemical conversion tank filled with a phosphoric acid aqueous solution as an electrolytic aqueous solution, and the other end of the anode lead is connected to the anode body of the chemical conversion tank. Then, by performing anodization, a uniform dielectric layer of tantalum oxide (Ta2O5) is formed on the surface of the anode body (the surface of the porous sintered body including the inner wall surface of the pores) and the surface of a portion of the anode lead.
[0110] Next, 3,4-ethylenedioxythiophene, iron (III) p-toluenesulfonate and 1-butanol, which are raw materials of the first conductive polymer, are mixed to prepare a dispersion (reaction solution) containing the first monomer. After the anode body is immersed in the dispersion, the anode body is lifted out of the dispersion and heat-treated in the atmosphere. In this case, iron (III) p-toluenesulfonate functions as an oxidant. In this way, the first monomer is polymerized on the dielectric layer to form a solid electrolyte layer containing poly (3,4-ethylenedioxythiophene) (PEDOT) as the first conductive polymer layer.
[0111] Next, after washing the anode body on which the first conductive polymer layer is formed, poly(3,4-ethylenedioxythiophene) as the second conductive polymer and p-toluenesulfonate are mixed to prepare a second dispersion. After the anode body is immersed in the second dispersion, the anode body is pulled out from the second dispersion to allow the second dispersion to permeate the anode body. Then, a drying treatment is performed under atmospheric pressure to form a second conductive polymer layer.
[0112] A carbon paste and a metal paste were sequentially applied to a predetermined region on the surface of the second conductive polymer layer to form a cathode layer composed of a carbon layer and a silver paste layer, thereby obtaining a capacitor element.
[0113] An anode lead frame and a cathode lead frame are arranged on the capacitor element, and they are sealed with sealing materials a1 to a7 to form an outer casing. Then, the anode lead frame and the cathode lead frame protruding from the outer casing are bent along the outer casing to obtain solid electrolytic capacitors E1 to E7.
[0114] Sealing materials a1 to a7 are thermosetting epoxy resin compositions containing epoxy resin as a main resin. As fillers, silicon dioxide (SiO2) particles and magnesium hydroxide (Mg(OH)2) particles are mixed and used so that the pH value of the sealing material solution is the value shown in Table 1.
[0115] Comparative Example 1
[0116] A solid electrolytic capacitor C1 was obtained in the same manner as in Example 1 except that a sealing material b1 containing only silicon dioxide particles and no magnesium hydroxide particles was used as a filler.
[0117] Comparative Example 2
[0118] Solid electrolytic capacitor C2 was obtained in the same manner as in Example 1 except that sealing material b2 was used. Compared with any of sealing materials a1 to a7, the content of silicon dioxide particles in the filler was increased and the content of magnesium hydroxide particles was decreased so that the pH value of the elution solution of sealing material b2 was as shown in Table 1.
[0119] The following evaluations were performed on the produced solid electrolytic capacitors of Examples and Comparative Examples.
[0120] [evaluate]
[0121] In an environment of 20°C, using a 4-terminal LCR tester, the initial electrostatic capacitance C0 (F) of the solid electrolytic capacitors of the embodiments and comparative examples was measured in two states: a case where a voltage 0.8 times the rated voltage was applied and a case where no voltage was applied. For each embodiment and each comparative example, 60 solid electrolytic capacitors were made. The initial electrostatic capacitance C0 (F) is the average value of 30 with voltage applied and 30 without voltage applied.
[0122] Next, 60 solid electrolytic capacitors were arranged in an environment of 110°C / relative humidity 85%, and a voltage of 0.8 times the rated voltage was continuously applied to 30 solid electrolytic capacitors. No voltage was applied to the remaining 30 solid electrolytic capacitors. The solid electrolytic capacitors were recovered after 132 hours, and the average value of the electrostatic capacitance C1 (F) of the 30 solid electrolytic capacitors to which voltage was continuously applied and the average value of the electrostatic capacitance C2 (F) of the 30 solid electrolytic capacitors to which no voltage was applied were calculated. Based on each average value, the rate of change of electrostatic capacitance C1 and electrostatic capacitance C2 relative to the initial electrostatic capacitance C0 was calculated. The results are shown in Table 1.
[0123] Next, 60 solid electrolytic capacitors of each embodiment and each comparative example prepared separately were arranged in an environment of 85°C / relative humidity 85%, and a voltage of 0.8 times the rated voltage was continuously applied to 30 solid electrolytic capacitors. No voltage was applied to the remaining 30 solid electrolytic capacitors. The solid electrolytic capacitors were recovered after 1000 hours, and the average value of the electrostatic capacitance C3 (F) of the 30 solid electrolytic capacitors to which voltage was continuously applied and the average value of the electrostatic capacitance C4 (F) of the 30 solid electrolytic capacitors to which no voltage was applied were calculated. Based on each average value, the rate of change of electrostatic capacitance C3 and electrostatic capacitance C4 relative to the initial electrostatic capacitance C0 was calculated. The results are shown in Table 1.
[0124] [Table 1]
[0125]
[0126] As shown in Table 1, in an experiment assuming the use of a solid electrolytic capacitor in a severe high temperature and high humidity environment (110°C / relative humidity 85%), when the pH value of the elution solution of the sealing material is above 6.0 and below 8.1, the electrostatic capacitance of the solid electrolytic capacitor does not change significantly even if voltage is continuously applied, and the electrostatic capacitance hardly decreases.
[0127] On the other hand, when the pH value of the sealing material eluate was less than 6, the electrostatic capacitance decreased significantly when the voltage was applied for only 132 hours in an environment of 110° C. / relative humidity 85%.
[0128] It should be noted that it can be understood that, even if the voltage is continuously applied to the solid electrolytic capacitor with a sealing material pH value of less than 6.0 under an environment of 85°C / 85% relative humidity, the reduction in electrostatic capacitance will not be the same as the test under an environment of 110°C / 85% relative humidity if it does not pass 1000 hours. At the moment of 132 hours, no significant change in capacitance was seen, ensuring sufficient electrostatic capacitance.
[0129] The present invention has been described by the present preferred embodiments, but such disclosure should not be construed in a limiting sense. Various modifications and changes will undoubtedly be apparent to those skilled in the art in the art to which the present invention belongs by reading the above disclosure. Therefore, the appended claims should be interpreted as including all modifications and changes without departing from the true spirit and scope of the present invention.
[0130] Industrial Applicability
[0131] The present disclosure can be applied to a solid electrolytic capacitor used in a high-temperature and high-humidity environment.
[0132] Description of Reference Numerals
[0133] 20: solid electrolytic capacitor; 10: capacitor element; 1: anode body; 2: anode wire; 2a: first part; 2b: second part; 3: dielectric layer; 4: solid electrolyte layer; 5: cathode layer; 5a: carbon layer; 5b: conductive resin layer; 6: anode part; 7: cathode part; 8: conductive adhesive material; 11: outer body (sealing material); 13: anode lead frame; 14: cathode lead frame; 14a: joint part.
Claims
1. A solid electrolytic capacitor comprising: A capacitor element having an anode portion and a cathode portion; an anode lead frame connected to the anode portion; a cathode lead frame connected to the cathode portion; and an insulating sealing material covering the capacitor element and partially covering the anode lead frame and the cathode lead frame, The capacitor element comprises a solid electrolyte, 5 g of the sealing material was immersed in 50 cc of water or methanol aqueous solution having a pH value of 7.0 in a pressure-resistant container, and the pH value of the water or methanol aqueous solution after heating at 121° C. for 24 hours was 6.0 or more and 8.1 or less.
2. The solid electrolytic capacitor according to claim 1, wherein: The pH value of the water or methanol aqueous solution after heating at 121° C. for 24 hours is 6.5 or more.
3. A solid electrolytic capacitor comprising: A capacitor element having an anode portion and a cathode portion; an anode lead frame connected to the anode portion; a cathode lead frame connected to the cathode portion; and an insulating sealing material covering the capacitor element and partially covering the anode lead frame and the cathode lead frame, The capacitor element comprises a solid electrolyte, The sealing material is immersed in water or methanol aqueous solution having a pH value of 7.0 in a pressure-resistant container, and heated until the pH value of the water or methanol aqueous solution exceeds 7 after saturation of the eluted components from the sealing material.
4. The solid electrolytic capacitor according to claim 1 or 3, wherein: The sealing material comprises a filler, The filler comprises a metal hydroxide.
5. The solid electrolytic capacitor according to claim 4, wherein: The metal hydroxide includes at least one of magnesium hydroxide and aluminum hydroxide.
6. The solid electrolytic capacitor according to claim 4, wherein: The filler may further include inorganic powders other than the metal hydroxide.
7. The solid electrolytic capacitor according to claim 6, wherein: The inorganic powder other than the metal hydroxide includes a metal oxide.
8. The solid electrolytic capacitor according to claim 6, wherein: In the sealing material, the content of the inorganic powder other than the metal hydroxide is greater than the content of the metal hydroxide.
9. The solid electrolytic capacitor according to claim 7, wherein: The metal oxide includes at least one selected from the group consisting of aluminum oxide, magnesium oxide, silicon oxide, titanium oxide, and zirconium oxide.
10. The electrolytic capacitor according to any one of claims 1 to 9, wherein The content of the filler in the sealing material is 80% by mass or more.
Citation Information
Patent Citations
Epoxy resin molding material for sealing electronic part and electronic part
JP1998259292A
Solid electrolytic capacitor and improved method for manufacturing solid electrolytic capacitor
JP2016522573A